A Sociological Analysis of the Phenomenon of Santri Deviating from the Purpose of Qur’anic Study toward Other Activities - Arini Nurlaela; Rini; Adinda Anatya; Zidny Ilham Tauhid; Ai Ilis (Institut KH Ahmad Sanusi (INKHAS) Sukabumi, 2026)
The phenomenon of students deviating from the primary goal of studying religious texts to engage in other activities has become an interesting social issue to examine, especially in the context of pesantren education. This study aims to analyze the sociological factors underlying such behavior and the efforts to address it. The research uses a qualitative approach with a case study method in one of the pesantren. Data were collected through interviews, observations, and documentation. The results show that peer influence, routine fatigue, and lack of social control are the dominant causes. As stated by one of the pesantren caretakers, who also serves as the head of security, there is a need for a persuasive approach and exemplary behavior from the administrators to redirect students back to their primary objectives. This study recommends the importance of group-based counseling guidance and instilling discipline values through role modeling.